2018
DOI: 10.1002/pc.25029
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the electrical conductivity of polyetherimide‐based foams by simultaneously increasing the porosity and graphene nanoplatelets dispersion

Abstract: Significant improvement in electrical conductivity of graphene nanoplatelets‐filled polyetherimide (PEI) foams was achieved by simultaneously increasing the porosity and graphene nanoplatelets dispersion. Foams were prepared by means of water vapor‐induced phase separation using a concentration of graphene nanoplatelets (GnP) between 1 and 10 wt%. To obtain two sets of foams having different density and porosity, PEI's concentration in N‐methyl pyrrolidone (NMP) solvent prior to foaming was set at 15 and 25–30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…As can be seen, the electrical conductivity of the foams increased by six orders of magnitude, reaching 3.45 × 10 −10 S/m with the addition of only 1.5 wt % (0.35 vol %) GnP. Interestingly, this value was clearly higher than those obtained for foams containing the same amount of GnP prepared by WVIPS method [6]. Since ultrasonication was used in both cases, this result could indicate an enhanced dispersion of GnP nanoparticles via melt-mixing and formation of a more effective conductive network throughout the foam using one-step scCO 2 foaming.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the electrical conductivity of the foams increased by six orders of magnitude, reaching 3.45 × 10 −10 S/m with the addition of only 1.5 wt % (0.35 vol %) GnP. Interestingly, this value was clearly higher than those obtained for foams containing the same amount of GnP prepared by WVIPS method [6]. Since ultrasonication was used in both cases, this result could indicate an enhanced dispersion of GnP nanoparticles via melt-mixing and formation of a more effective conductive network throughout the foam using one-step scCO 2 foaming.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the value of n for randomly distributed spherical-shaped particles has been proposed to be equal to 1/3 [48], while the value of n = 1 corresponds to a 3D random fibre network [49]. We have shown in our previous works [4,6] that assuming a tunnel-like approach for PEI-GnP foams prepared using WVIPS led to a value of n equal to 1/5, which, according to Krenchel [50] and Fisher et al [51], could confirm the existence of a conductive network formed by GnP with a 3D random distribution. Similarly, in this work the best fit was obtained using an n value of 1/5 (see fitting representation in Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Foaming of these nanocomposites has been the center of attention with the goal of creating novel foams with improved specific properties. In this sense, we have previously investigated thoroughly the preparation and properties of foams based on other high performance thermoplastics like polyetherimide (PEI) reinforced with GnP and carbon nanotubes [28][29][30][31]. The results presented in these works indicate that foaming provided further enhancement of the electrical conductivity by promoting a better dispersion of the nanofillers through the continuous phase of the nanocomposite foams [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, this model is sensitive to the concentration range of GnP and does not consider that nanocomposites could already present a level of electrical conduction at GnP concentrations below the critical value, as can be seen in Figure 4. Therefore, a tunnel conduction mechanism was suggested as the dominant model in the GnP concentration range used in this study, since it has been previously demonstrated to be a better fitting model for cellular materials containing conductive fillers [20,21,23,29] before the formation of a continuous conductive particle network. Considering a tunnel conduction mechanism, the electrical conductivity could be predicted using: As can be seen in Figure 3, the electrical conductivity increased for all the microcellular nanocomposites with the addition of GnP, reaching values as high as 8.2 × 10 −2 S/m with 2.7 vol% (10 wt%) graphene nanoplatelets in 15PSU.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…Recent focus on creating cellular nanocomposites containing conductive nanoparticles has led to the development of novel materials with improved specific properties-for instance, in terms of electrical and thermal conductivities. Regarding this matter, studies microcellular nanocomposites based on polyetherimide filled with carbon-based nanofillers have been recently published [19][20][21][22][23]. In this sense, we have previously reported the thermal conductivity behavior of PSU-based cellular nanocomposites containing graphene nanoplatelets [24].…”
Section: Introductionmentioning
confidence: 98%